Pengaruh Kemampuan Menyusun Laporan Keuangan, Literasi Keuangan dan Teknologi Informasi Terhadap Kinerja UMKM: Kasus UMKM Mebel di Kabupaten Karanganyar - Anugrah Akbar Wibowo; Suprihatmi Suprihatmi; Setyaningsih Setyaningsih (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to analyze the significance of the effect of the ability to prepare financial reports, financial literacy and information technology on the performance of furniture MSMEs in Karanganyar Regency. This type of research is quantitative research. Data collection techniques are questionnaires, observations, interviews whose results are then processed using the SPSS version 26 program using data analysis techniques classical assumption test, multiple linear regression analysis, descriptive analysis, t test, F test, and coefficient of determination. The population in this study were 464 Karanganyar Regency furniture MSMEs registered with the One-Stop Investment and Integrated Services Office in 2022. The sample size using the slovin formula obtained a sample of 83 MSMEs. The sampling technique used simple The results of this study indicate that the t test obtained the results of the ability to prepare financial reports has a significant effect on the performance of furniture MSMEs in Karanganyar Regency. Financial literacy has no significant effect on the performance of MSMEs in Karanganyar Regency. Information technology has a significant effect on the performance of MSMEs in Karanganyar Regency. The results of the F test showed that there was a significant influence on the ability to prepare financial reports, financial literacy, and information technology. The results of the calculation of the coefficient of determination obtained Adjusted R^2 = 0.340, meaning that 66 percent of the income of furniture MSMEs in Karanganyar Regency is influenced by the ability to prepare financial reports, financial literacy, and information technology.